Domestic Value Added in Exports: Theory and Firm Evidence from China - Hiau Looi Kee; Heiwai Tang (Center for Economic Studies and ifo Institute (CESifo), 2015)
China has defied the declining trend in domestic content in exports in many countries. We study China's rising domestic content in exports using firm- and customs transaction-level data. Our approach embraces firm heterogeneity and hence reduces aggregation bias. We find that the substitution of domestic for imported materials by individual processing exporters caused China's domestic content in exports to increase from 65% to 70% in 2000-2007. Such substitution was induced by the country's trade and investment liberalization, which deepened its engagement in global value chains and led to a greater variety of domestic materials becoming available at lower prices.
Keywords: F10; F14; 330; firm heterogeneity; domestic value added; value added trade; China; global value chains; trade liberalization; FDI liberalization